An investigation into the role of a Childrens' Rights Education program in a diverse, urban, DEIS school, focusing on an Intercultural perspective. Is it a good fit? An action-research and self-reflective study. - Dunphy, Elaine (My University, 2019)
This study investigates the ‘fit’ of a Childrens’ Rights Education program, in a diverse, urban, designated disadvantaged (DEIS) school. The program in this study is ‘Making Rights Real’ which was distributed to all schools in Ireland at the beginning of 2019. I ran the program in my First class of 22 children and is a diverse, multicultural group aged between 6-7. An action-research and self-study approach was undertaken for this study as these often work together. The action-research was teaching the program ‘Making Rights Real’ and I engaged in deeply-reflective journaling pre, during and post teaching the program. As the focus of this study is the ‘self’, I learned a lot about my own teaching pedagogies and the benefit reflective practice has on my overall teaching. The Making Rights Real program worked well in the context of the class and the children engaged enthusiastically with it. The program is a very good introduction to Childrens Rights, however Human Rights Education would need to be developed to further extend the learning in the future.
Master in Intercultural Education
Keywords: Research Subject Categories; Childrens' Rights Education program; Designated disadvantaged (DEIS) school; Making Rights Real for Children: A Children's Rights Audit of Irish Law.; Childrens Rights; Human Rights Education